2018
DOI: 10.1021/acsmedchemlett.8b00369
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Potent Dimeric Positive Allosteric Modulators at the Ligand-Binding Domain of the GluA2 Receptor

Abstract: The ionotropic glutamate receptor GluA2 is considered to be an attractive target for positive allosteric modulation for the development of pharmacological tools or cognitive enhancers. Here, we report a detailed structural characterization of two recently reported dimeric positive allosteric modulators, TDPAM01 and TDPAM02, with nanomolar potency at GluA2. Using X-ray crystallography, TDPAM01 and TDPAM02 were crystallized in the ligandbinding domain of the GluA2 flop isoform as well as in the flip-like mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Glutamate Receptor Ion Channels revealed that different PAMs can have distinct binding modes at different subsites within the ABD dimer interface (Sun et al, 2002;Jin et al, 2005;Kaae et al, 2007;Hald et al, 2009;Ptak et al, 2009;Sobolevsky et al, 2009;Timm et al, 2011;Krintel et al, 2013;Norholm et al, 2013;Goffin et al, 2018;Laulumaa et al, 2018). This discovery has stimulated development of newer classes of modulators with improved potency (Kaae et al, 2007;Pohlsgaard et al, 2011;Ptak et al, 2014;Laulumaa et al, 2018) (Section IX. Exogenous Positive and Negative Allosteric Modulators).…”
Section: B the Extracellular Agonist Binding Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutamate Receptor Ion Channels revealed that different PAMs can have distinct binding modes at different subsites within the ABD dimer interface (Sun et al, 2002;Jin et al, 2005;Kaae et al, 2007;Hald et al, 2009;Ptak et al, 2009;Sobolevsky et al, 2009;Timm et al, 2011;Krintel et al, 2013;Norholm et al, 2013;Goffin et al, 2018;Laulumaa et al, 2018). This discovery has stimulated development of newer classes of modulators with improved potency (Kaae et al, 2007;Pohlsgaard et al, 2011;Ptak et al, 2014;Laulumaa et al, 2018) (Section IX. Exogenous Positive and Negative Allosteric Modulators).…”
Section: B the Extracellular Agonist Binding Domainmentioning
confidence: 99%
“…For other PAMs, such as aniracetam and CX614, one molecule binds but with two overlapping conformations in a more central site within the dimer interface (Jin et al, 2005;Krintel et al, 2013;Goffin et al, 2018). Finally, the PAM N,N 0 -(1,4-Phenylenedi-2,1-ethanediyl)bis-2-propanesulfonamide (CMPDA) has a symmetrical chemical structure and binds to a central site (Kaae et al, 2007;Sobolevsky et al, 2009;Timm et al, 2011;Laulumaa et al, 2018). The AMPA receptor PAMs increase the stability of the ABD dimer interface to slow the transition into the desensitized state, and a subset of PAMs also slows receptor deactivation (Jin et al, 2005;Mitchell and Fleck, 2007;Partin, 2015;Shaffer et al, 2015).…”
Section: Ampa Receptor Positive Modulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are active in vitro as AMPAR PAMs with nanomolar potency at GluA2, and they were also found to interact on both sites of the GluA2-LBD dimer interface. 13,14 In the present paper, we disclose the results of our studies on a new series of AMPAR PAMs designed using the classical isosteric replacement concept. 15,16 We have here focused our efforts on the replacement of the two nitrogen atoms of the thiadiazine ring by carbon atoms, leading to the preparation of thiochroman 1,1-dioxides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Finally, a structure-based approach led to the preparation of dimers 6 and 7 . These compounds are active in vitro as AMPAR PAMs with nanomolar potency at GluA2, and they were also found to interact on both sites of the GluA2-LBD dimer interface. , …”
Section: Introductionmentioning
confidence: 99%